Investigating the Difficulties and Strategies of The EFL Students in Translating Indonesian English - Syukrina Syukrina (JADEs Journal of Academia in English Education, 2021)
The aims of this study were to investigate the difficulties encountered by the EFL students at English Department of IAIN Langsa, as well as the strategies they utilised in translating Indonesian text into English. This research employed a qualitative approach with the technique applied purposive sampling. The researcher had ten sixth-semester students of English Education majors at IAIN Langsa as the subjects. Documentation and interview were employed as the instruments to collect data. Based on the outcomes of the two data, demonstrated that all of the students experienced difficulties in translating the text. The difficulties they encountered were related to: 1) Vocabularies particularly regarding religious terms, 2) Grammar, (3) Equivalence, and (4) problematic assorting the long sentence. They revealed that the lack of knowledge and seldom employing the certain vocabularies like religious terms in daily life that caused them felt difficult in translating the text. Meanwhile, the output of the interview expressed that the students employed three strategies to superintend the translation difficulties, namely : 1) Natural Borrowing Strategy, (2). Adaptation Strategy, and (3). Literal Translation Strategy. The students gained that these strategies were appropriate and simple for them to apply in overcoming difficulties during the translation process.